The Use Of DuPont System To Measure Profitability Performance (Case Research Cigarette Company On Listed Indonesia Stock Exchange 2008-2011) - Hartoko, Yoga Widya (Jurnal Ilmiah Mahasiswa FEB, 2013)
This research aims to know the trend analysis profitability perfomance byusing DuPont System  in  cigarette  company. The  data  used  in  this research issecondary data. For assessing the perfomance of company financial condition, theresearch used time series analysis. Time series analysis provides the hints on howto evaluate by comparing  the  financial  ratios of  the company from one period  toanother. It could be concluded that there have been different results of profitabilityperformance  in each company. The highest  results from DuPont System for fourconsecutive years from three companies were found in the Corner Indonesia StockExchange  (IDX) Brawijaya University  in Malang obtained PT HM SampoernaTbk.Keywords : DuPont System, Cigarette Company,  Time Series Analysis.